Characterization of Birnin Gwari Gold Sand for its Appraisal for Gold Recovery - Alaba, Olanrewaju C.; Alabi, Oladunni O.; Mbuyi , Melodi.M; Oseni, Bamidele M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Characterization is a vital step in material analysis, bridging the gap between material structure, processing methods and real-world applications. Crude gold samples were carefully sourced from Birnin Gwari pits in Kaduna State. Then proceeded to crush and homogenize them to sizes ranging between 3 to 5 mm using both manual and laboratory equipment. The samples were meticulously prepared for chemical and mineralogical analysis using the atomic absorption spectrophotometer (AAS), the energy X-ray fluorescence spectrometer (ED-XRFS), the X-ray diffractometer (XRD) the scanning electron microscope paired with the energy dispersive X-ray spectrometer (SEM-EDS) and the Leica petrographic microscope. The AAS assessment indicated a concentration of 118 ppm, in the ore sample validating its mining potential. However, the gold content in the ore is extremely low and cannot be detected easily; it is not found in its natural form based on ED-XRFS analysis results. The sample displayed diffraction patterns corresponding to a variety of minerals present based on XRD analysis. In addition, the SEM-EDS examination validates the presence of alumina, silica, and potassium oxide in the ore. The petrological study revealed that the mineral compositions, in the ore are closely interlocked with grain boundaries with quartz being identified as the gangue mineral.